Winners and losers from China’s ascension in international trade: a structural approach - Costa, Francisco Junqueira Moreira da (2019)
This paper employs a unified theoretical framework to estimate the effect ofchanges within China on the Brazilian and World’s economy. Based on the Ricar-dian model of trade of Costinotet al.(2012), we perform counterfactuals exercises toanalyze how industries in Brazil would have performed in the absence of the Chineseascension. We discuss two main counterfactual exercises. First, we model produc-tivity growth in China as the main lever by which Chinese supply and demandconditions evolve and affect economies worldwide. Second, we study how changesin composition of Chinese demand (taste) affects trade flows around the world. Thetwo counterfactual exercises together suggest that changes in China’s comparativeadvantage hampered manufacturing sectors abroad, in particular labor-intensiveBrazilian manufacture producers. We find no support for the idea of a China tasteshock driving demand towards raw materials. Our model suggests that if Chinatriggered a commodity boom in the world, or at least in Brazil, this was drivenmostly by increased income in China. And any changes in China’s tastes over prod-ucts contributed to moderate such boom. Specifically, our model indicates that theboom of soybeans cultivation in Brazil is due to changes in Brazilian comparativeadvantage paired with a level increase in demand for this product within China.